Pengaruh Kepemimpinan dan Kompensasi Terhadap Semangat Kerja Karyawan dan Kinerja Karyawan Pada PT. United Indobali Denpasar - Dharma Putra, I Gede Agus Ary; Putra, Made Surya (E-Jurnal Manajemen, 2013)
Employees are important assets to the company, therefore the company must pay attention to the performance of the employees. There are several factors that affect the performance and the morale of employee, where morale is influenced by the leadership and compensation. The research objective was to investigate the influence of leadership and compensation  to employee morale and performance at PT. United Indobali Denpasar. The population were 235 people, using the Slovin formula, it found 148 sample, selection of respondents using stratified random sampling. Data collection methods were using observation, questionnaires and interviews. Data was  processed using path analysis techniques with SPSS (Statistical Package for Social Science). Results showed leadership and compensation has a positive relationship to employee morale and employee performance. Keyword :       Leadership, Compensation, employee morale , employee performance